Pendampingan Pengunaan Media Audio-Visual dalam Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Efektivitas Pembelajaran di MTs AZ-Zainiyah I Paiton Probolinggo - Zubaidi, Ahmad; Putri Handayani; Halimatus Sa'diyah; Hamidah Akilla; Laelatol Mafiroh (Lembaga Riset dan Inovasi Al-Matani, 2024)
This service aims to improve the effectiveness and quality of Islamic Religious Education (PAI) teaching at MTs AZ-Zainiyah I Paiton Probolinggo through the accompaniment in the use of audio-visual media. The method used is Community Service (PKM) activities involving several stages: preparation and planning, training in the use of audio-visual media, preparation of lesson plans (RPP), implementation of audio-visual media in teaching, evaluation and monitoring, and reporting and dissemination of results. In the preparation and planning stage, needs identification and activity planning are carried out involving PAI teachers and the school principal. Training is provided to PAI teachers to operate and integrate audio-visual media into teaching. The lesson plans are then prepared by integrating the media. Implementation is conducted in the classroom with observations from the PKM team to ensure the effectiveness of the application. Evaluation and monitoring are conducted to measure results and provide feedback. This activity concludes with the preparation of reports and publication of results. The results of this service show an increase in student interest and participation in PAI learning. Teachers also show improved ability to integrate the media into teaching. Evaluation indicates a significant improvement in the quality of learning. From the results of this service, it can be concluded that the accompaniment in the use of audio-visual media is effective in enhancing the effectiveness and quality of PAI teaching at MTs AZ-Zainiyah I Paiton Probolinggo.